A game theory approach for optimum strategy of the owner and contractor in delayed projects - Khanzadi, Mostafa; Eshtehardian, Ehsan; Chalekaee, Alireza (Journal of Civil Engineering and Management, 2016)
Delay is one of the problems occurring between owners and contractors. Deviation from base plans can be found using project control methods, continuous assessment of the schedule, determining progress percentages and earned value parameters. In such circumstances, conflicts might arise between contractor and owner as restoring project’s original schedule needs added expenditures by the contractor. Moreover, continuation of the previous procedure and late completion of the project will cause the owner damage. In this research, a mathematical model using game theory has been presented. The model investigates the behaviour and strategies of the parties involved in a delayed project through bargaining. It helps owners and contractors gain deeper understanding of the given delay problem, get a fairly accurate analysis of their situation and consider possible strategies in facing with such circumstances without spending a long and inconclusive time. The points which both parties can agree rationally proposed with a numerical example. Results of the model indicate that parameters involved in the problem are effective in changing the range width of negotiation. In special cases, such as disproportionate delay penalty, these parameters even make it neutral in negotiation. Step by step analysis of the model showed which features can threaten negotiation.